BG-12 in Multiple Sclerosis - Phillips, J. Theodore; Fox, Robert J. (Seminars in Neurology, 2013)
Dimethyl fumarate (DMF) is an orally administered agent that has been used for over 40 years for the treatment of psoriasis. Recent work demonstrates both DMF immunomodulatory and neuroprotective actions in vitro and in animal models of autoreactive central nervous system inflammation and neurodegeneration. DMF acts through chemical modification of the repressor protein Keap1, allowing stabilization and nuclear translocation of the transcription factor Nrf2, with subsequent downstream activation of a cascade of several cytoprotective and antioxidant pathways. Additionally, suppression of transcription factor NF-κB-mediated proinflammatory signaling results in the inhibition of proinflammatory responses and induction of anti-inflammatory cytokines. BG-12 is an orally administered, enteric-coated microtablet preparation of DMF. In two phase III, relapsing-remitting multiple sclerosis (MS) trials, BG-12 led to a 44 to 53% reduction in annualized relapse rate and a 71 to 85% reduction in new T2 lesions on magnetic resonance imaging. The most common side effects of BG-12 are cutaneous flushing and gastrointestinal symptoms, with the highest incidence in the first month after starting treatment. No serious safety signals were seen during the phase II and III trials, including no increased risk of opportunistic infections or cancer. Altogether, BG-12's novel mechanism of action appears to provide a favorable balance of efficacy, safety, and tolerability for treatment of relapsing MS.
Keywords: multiple sclerosis; BG-12; dimethyl fumarate; fumaric acids; NF-E2-related factor 2